THE ROLE OF PHYSICAL EXERCISE IN REDUCING INFLAMMATION IN PATIENTS WITH SYSTEMIC SCLEROSIS - Aleksandra Gradek; Marcin Sawczuk; Dominika Nowak; Adam Zarzycki; Julia Tarnowska; Filip Szydzik; Bartosz Żegleń; Katarzyna Kozon; Monika Grudzień; Anna Leśniewska (International Journal of Innovative Technologies in Social Science, 2025)
Introduction and Aim: Systemic sclerosis (SSc) is a chronic, progressive disease that leads to multi-organ failure. In its pathogenesis, inflammation plays a significant role, particularly due to the reduced frequency of regulatory T cells that modulate this process. The aim of this paper was to analyze the available scientific evidence to determine how physical activity influences the reduction of inflammation and its relevance in the therapy of systemic sclerosis.Results: Systemic sclerosis is associated with a chronic inflammatory state, as indicated by elevated inflammatory markers such as C-reactive protein and ferritin, which correlate with disease severity and symptom progression. Physical activity demonstrates potential in modulating inflammation by lowering inflammatory markers and improving overall bodily function. Regular, supervised exercise in patients with SSc yields measurable benefits, enhancing exercise capacity, muscle strength, quality of life and respiratory function.Materials and Methods: During the writing of this paper, data analysis was conducted based on a review of available articles published in the PubMed database. The following combination of keywords was used: „sport in systemic sclerosis", „physical exercise in systemic sclerosis", "sport in systemic sclerosis”, „inflammation in systemic sclerosis” „inflammation and exercise”. The following filters were applied: Free full text, Clinical Trial, Randomized Clinical Trial and within the last 10 years.Conclusion: Chronic inflammation in systemic sclerosis accelerates the development of complications, while regular, moderate physical activity under supervision can improve physical capacity, microcirculation, and reduce inflammatory symptoms. However, further research is necessary to confirm the beneficial effects of exercise as a therapeutic intervention in systemic sclerosis.